Truncus arteriosus communis with intact ventricular septum. Issue 1 (July 1979) - Carr, I; Bharati, S; Kusnoor, V S; Lev, M
Abstract : This is the first documented case of truncus arteriosus communis with intact ventricular septum in which extensive clinical, haemodynamic, angiographic, and pathological data are available. Angiography suggested the presence of two discrete semilunar valves but necropsy showed a basically single semilunar valve. This case fills a gap in the spectrum of aorticopulmonary, truncal, and infundibular septal defects, and reinforces the belief that the essence of truncus arteriosus communis is a single semilunar valve, common to both ventricles, which need not be associated with the defects in the adjacent parts of the structural continuum.